EFFECTIVE COMMUNICATION IN TEAMWORK IN HEALTH: A CHALLENGE FOR PATIENT SAFETY - Jane Walkiria da Silva Nogueira; Maria Cristina Soares Rodrigues (Universidade Federal do Paraná, 2015)
This reflexive essay discusses effective communication from the perspective of multi-professional teamwork for quality of healthcare and patient safety. In the analysis of the object in question, it was identified that training programs for communication skills, practical simulations and standardized ways for presenting information on the patient constitute effective ways for overcoming barriers to efficacious communication. The adoption of strategies for improving the team's communication represents a challenge which requires change in the culture of patient safety in the health organizations.